Students’ Perceptions of the Effectiveness of Online Learning in Intensive Speaking Course - Fadilla, Andi Aenul; Muhayyang, Maemuna; Munir, Munir (State University of Makassar, 2025)
This study aims to investigate students' perceptions of the effectiveness of online learning in intensive speaking courses. The research method used is the descriptive-qualitative method. The participants in this study were students of the 2022 class of the English Language Education study program, Makassar State University for the 2022/2023 academic year. Eight students were selected as participants using a simple random sampling technique. The instrument of this research is an interview. Qualitative descriptive analysis was used to analyze the data collected in the interview transcripts. Overall, students have positive and negative perceptions of the effectiveness of online learning in intensive speaking courses. The students revealed that online learning in intensive speaking courses had positive and negative impacts on their learning process. Positive perceptions of online learning in intensive speaking courses include 1) increasing skills, 2) flexibility, and 3) increasing self-confidence. In contrast, the negative perceptions found from online learning in intensive speaking courses are 1) non-technical constraints, 2) technical constraints, and 3) lack of interaction. Even though students' perceptions varied, based on the data obtained, students' positive perceptions are more dominant than their negative perceptions. In addition, they all argued that online learning in intensive speaking courses was effective. Therefore, it can be concluded that online learning in intensive speaking courses is effective.Keywords— Intensive Speaking Course, Online Learning, Effectiveness, Students’ Perceptions